Objective moderate-to-vigorous physical activity in 1064 patients with COPD after stratification for gender, FEV1 and BMI - Mesquita, R.; Pitta, F.; Donaire-Gonzalez, D.; Deering, B.; Patel, M.; Mitchell, K.; Alison, J.; van Gestel, A.; Zogg, S.; Garcia-Aymerich, J.; Hill, K.; Romme, E.; et al. (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2013)
Background: Physical inactivity in COPD is associated with poor outcomes. Therefore, it is important to understand the determinants of moderate-to-vigorous physical activity (MVPA) in COPD. We aimed to assess the mean level of MVPA after stratification for gender, forced expiratory volume in the first second (FEV1) and body-mass index (BMI). Methods: In 1064 COPD subjects (716 men; age: 67±8 years; BMI: 27±6 kg• m-2; FEV1: 50±21 % predicted) from 14 centers, MVPA time was assessed using the SenseWear Armband activity monitor for ≥4 days. Gender, FEV1 and BMI were used for stratification. Results: In total, 6300 days with MVPA data were obtained, with a median (IQR) MVPA time of 27 (11-59) min• day-1. 47% of the subjects had a MVPA time ≥30 min• day-1. Men had a higher MVPA time than women (29 (12-63) versus 24 (9-52) min• day-1, respectively; p=0.002). Figure 1 presents the mean time in MVPA after stratification for GOLD classes and BMI in men (A) and women (B). Conclusions: This multicenter study showed that MVPA time generally is BMI-dependent (higher BMI results in lower MVPA) and GOLD-dependent (higher GOLD results in lower MVPA) in men and women with COPD.